Multivariate analysis in pollen parent (restorer line) of hybrid rice (Oryza sativa I.) - Hasan, MJ; Kulsum, Umma; Rahman, MH; Akter, A; Shamsuddin, AKM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 63-66